2016
DOI: 10.1016/j.actaastro.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent emissivity property in La0.7Sr0.3MnO3 films

Abstract: Thermochromic films have been deposited by magnetron sputtering technique on different substrates. The crystallinity and surface morphology of the films have been characterized. Characterization result shows that the films are of perovskite structure. Composition analysis is performed and the result indicated that the element composition of the film can be close to its stoichiometric ratio. Temperature-dependent reflectivity and emissivity are studied. Reflectivity spectra show a downward trend with increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…[146] Currently, the most popular perovskite oxide is lanthanum strontium manganite oxide (LSMO), which presents more efficient thermal emissivity modulation than other perovskite oxides. [143,147,148] For instance, Huang et al [143] investigated the infrared emissivity of bulk LSMO and its combinations with different metallic/dielectric gratings (Figure 9c). The results indicated that the bulk LSMO modulated the thermal emissivity from 0.10 to 0.65 (Case 1 in Figure 9d), while the LSMO integrated with Al and SiO 2 gratings (Case 4 in Figure 9d) achieved a higher emissivity modulation due to the local resonance structure.…”
Section: Thermo-responsive Materialsmentioning
confidence: 99%
“…[146] Currently, the most popular perovskite oxide is lanthanum strontium manganite oxide (LSMO), which presents more efficient thermal emissivity modulation than other perovskite oxides. [143,147,148] For instance, Huang et al [143] investigated the infrared emissivity of bulk LSMO and its combinations with different metallic/dielectric gratings (Figure 9c). The results indicated that the bulk LSMO modulated the thermal emissivity from 0.10 to 0.65 (Case 1 in Figure 9d), while the LSMO integrated with Al and SiO 2 gratings (Case 4 in Figure 9d) achieved a higher emissivity modulation due to the local resonance structure.…”
Section: Thermo-responsive Materialsmentioning
confidence: 99%
“…Li et al. [ 63,64 ] synthesized La 0.7 Ca 0.3− x Sr x MnO 3 compositions which exhibited tunable infrared properties and Δε reached 0.6 finally when heating it to 373 K. Yu et al. [ 65 ] prepared La 0.67 Ca 0.25 Sr 0.08 MnO 3 whose transition temperature decreased to 9 °C while the emissivity changed from 0.23 to 0.73 when temperature varied between −50 to 50 °C.…”
Section: Thermochromic Materialsmentioning
confidence: 99%
“…(3) 4-Subsequently, a trapezoidal integration [21][22][23] is performed under the curve to calculate the absolute absorptance of the material as shown in Equation 4.…”
Section: Figure 2 Sample Holder and Sic Samplementioning
confidence: 99%